Targeting DNA repair nucleases in cancer - Henderson, LR (2023)
The human enzyme Apollo/SNM1B is a 5′-3′ exonuclease implicated in two aspects of genome integrity, both the response to DNA damage, where it is proposed to play a role in double-strand break (DSB) and interstrand crosslink (ICL) repair and telomere maintenance, where it resects leading strand telomeres, generating overhangs contributing to telomeric protection. The first part of this study involved generating an SNM1B-disrupted human cell line and characterising this for defects in DNA repair processes. These experiments revealed unexpected sensitivities to agents that produce DNA damage that is repaired by homologous recombination, implying a role for SNM1B in this process. Further characterisation of this cell line’s telomeric phenotypes demonstrated that SNM1B is involved in regulating telomere length. Studies were also undertaken to explore the SNM1B interactome, which showed interactions between SNM1B and the Bloom syndrome helicase, and non-homologous end joining (NHEJ) components. The second part of this study details the development of inhibitors against the human SNM1 family of nucleases, particularly SNM1B. As these enzymes play critical roles in the response to DNA damage, compounds that inhibit them might have utility as standalone anti-proliferative agents in certain tumour types, or could be used as adjuncts to genotoxic chemotherapeutics, potentiating their effects or preventing resistance from arising. Initially, a high-throughput screen was carried out against SNM1A, which identified hydroxamic acid-containing compounds as general inhibitors of the SNM1 nucleases. Structure-guided optimisations of these compounds resulted in a highly potent inhibitor of SNM1B, which displays impressive target selectivity. To combat a lack of cell permeability, a prodrug analogue of this compound was generated, which was cytotoxic across malignant and non-malignant cell lines. p53 status was found to be a significant determinant of sensitivity to this compound, revealing an under-appreciated aspect of the biology of SNM1B.